Neuerwerbungen : 1979. - Städtisches Kunstmuseum Bonn (Bonn : Städtisches Kunstmuseum Bonn, 1980)
Macke, August ; Campendonk, Heinrich ; Engert, Ernst Moritz ; Feldmann, Otto ; Henseler, Franz Seraph ; Macke, Helmuth ; Seehaus, Paul Adolf ; Thuar, Hans ; Seehaus, Paul Adolf ; Beuys, Joseph ; etc.
Neuerwerbungen : 1979, Städtisches Kunstmuseum Bonn, 13.5. - 27.7.1980
boek